Knowledge and practices of pregnant women in relation to zoonoses by pets - Garaycochea, Alejandra (2020)
The aim of this study was to determine knowledge and practices related to zoonoses transmitted by companion animals among pregnant women who were treated at the National Maternal and Perinatal Institute of Lima, Peru. A survey was used that included demographic information of the person surveyed, possession and handling of pets, and knowledge and practices potentially associated with zoonosis transmission. A total of 250 surveys were collected. Results showed that 87.2 and 46.8% of pregnant women mentioned having dogs and cats, respectively, and 93.6 and 94.9% have them as pets, respectively. Also, 91.6% of respondents said they did not know or have heard the word zoonosis; however, 82.8% said they know that there are diseases that are transmitted from animals to people. Additionally, 57.2% of respondents indicated that pets can cause health problems during pregnancy and 44% considered hairs as an element of disease transmission. Habits with pets varied among respondents before and after pregnancy. The knowledge of the main zoonotic diseases potentially transmissible to pregnant women and their form of transmission was low, except for rabies.